Waiting for the Breeder - Manne, Alan S. (Review of Economic Studies, 1974)
This paper is addressed to the selection of an optimal mix of electricity generating plants. The focus is on the problem of uncertainty with respect to the date of availability of breeder nuclear reactors. Sequential probabilistic linear programming is employed. This makes it possible to optimize the mix of fossil, nuclear, and peaking plants to be installed during the 1980's – assuming that breeder technology will become available at some randomly determined later date. The model allows for the effects of exhausting our reserves of uranium ore. The exhaustion of these resources does not lead to disaster in the 21st century for an economy or a world with a backstop technology such as coal-fired electricity plants. There seems to be a low value of information on the breeder availability date, for the initial policy is rather insensitive to this date. This conclusion holds not only when future demands are taken as fixed parameters, but also when they are dependent upon the price of electricity. On environmental grounds (climate changes radioactivity hazards, air and water pollution), there may be good reasons to slow the rate of growth of electricity demand. These are quite different issues than exhausting the resources of low-cost uranium ore. If our numerical assumptions are correct, it is not optimal to slow down the electricity growth rate up to 1990 just because of possible delays in the arrival of the breeder and hence a rapid rise in the price of uranium. For the year 2000, the decision on demands can be deferred until the time arrives to make capital investment decisions for the decade following 1990. By that point, some of the breeder's uncertainties will have been resolved.